2017
DOI: 10.3389/fphys.2017.00828
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Regulation of Thyroid Hormone Metabolism Target Genes during Non-thyroidal Illness Syndrome Triggered by Fasting or Sepsis in Adult Mice

Abstract: Fasting and sepsis induce profound changes in thyroid hormone (TH) central and peripheral metabolism. These changes affect TH action and are called the non-thyroidal illness syndrome (NTIS). To date, it is still debated whether NTIS represents an adaptive response or a real hypothyroid state at the tissue level. Moreover, even though it has been considered the same syndrome, we hypothesized that fasting and sepsis induce a distinct set of changes in thyroid hormone metabolism. Herein, we aimed to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…45,46 When the levels of circulating THs are low, high levels of local T3 in hypothalamic cells inhibit the expression of TRH and downregulate TSH activity directly. 47,48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 When the levels of circulating THs are low, high levels of local T3 in hypothalamic cells inhibit the expression of TRH and downregulate TSH activity directly. 47,48…”
Section: Discussionmentioning
confidence: 99%
“…45,46 When the levels of circulating THs are low, high levels of local T3 in hypothalamic cells inhibit the expression of TRH and downregulate TSH activity directly. 47,48 Although a decrease in THs may be an adaptive response to critical illness, like fasting, 36 low levels of THs have been demonstrated to be associated with high mortality. Researchers have tried to give patients T3, LT4, TRH, GH-releasing peptide-2, and growth hormone-releasing hormone as TH replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Although other specific factors and pathways that regulate MCT8 (and MCT10) expression, especially in physiological relevant tissues, remain to be identified, several studies may provide some guidance for identifying such mechanisms. Recent studies in rodents indicated that expression both of Mct8 and Mct10 is responsive to feeding status and systemic inflammation because pronounced downregulation of hepatic and hypothalamic Mct8 expression levels was found during fasting (225)(226)(227) and reduced Mct8 expression in liver and brain vasculature during systemic inflammation (111,225).…”
Section: Reviewmentioning
confidence: 99%
“…The relative sequence and importance of these various mechanisms in depressing the HPT axis and thyroid hormone function in different tissues and phases of critical illness are the subject of most NTIS publications ( 10 , 104 , 105 ). Notwithstanding the effect of other mechanisms, alterations in the activity of the deiodinase enzymes lead to a decrease in T3 and an increase in rT3 and thus a reduction in thyroid hormone function in peripheral tissues during prolonged critical illness [based on biopsies on ICU patients who died ( 142 ) and studies on mice ( 143 , 144 )]. Circulating thyroid hormone concentrations, however, only reveal the “tip of the iceberg” of the alterations occurring at the tissue level ( 141 , 145 ), which thus are often missed altogether in clinical settings ( 146 ).…”
Section: A “Vicious Circle” Perpetuating Illnessmentioning
confidence: 99%